The Effect of Various Salinities and Light Intensities on the Growth Performance of Five Locally Isolated Microalgae [Amphidinium carterae, Nephroselmis sp., Tetraselmis sp. (var. red pappas), Asteromonas gracilis and Dunaliella sp.] in Laboratory Batch Cultures - George N. Hotos (MDPI AG, 2021)
After a 1.5-year screening survey in the lagoons of Western Greece in order to isolate and culture sturdy species of microalgae for aquaculture or other value-added uses, as dictated primarily by satisfactory potential for their mass culture, five species emerged, and their growth was monitored in laboratory conditions. Amphidinium carterae, Nephroselmis sp., Tetraselmis sp. (var. red pappas), Asteromonas gracilis, and Dunaliella sp. were batch cultured using low (20 ppt), sea (40 ppt), and high salinity (50 or 60 or 100 ppt) and in combination with low (2000 lux) and high (8000 lux) intensity illumination. The results exhibited that all these species can be grown adequately in all salinities and with the best growth in terms of maximum cell density, specific growth rate (SGR), and biomass yield (g dry weight/L) at high illumination (8000 lux). The five species examined exhibited different responses in the salinities used, whereby Amphidinium clearly performs best in 20 ppt, far better than 40 ppt, and even more so than 50 ppt. Nephroselmis and Tetraselmis grow almost the same in 20 and 40 ppt and less well in 60 ppt. Asteromonas performs best in 100 ppt, although it can grow quite well in both 40 and 60 ppt. Dunaliella grows equally well in all salinities (20, 40, 60 ppt). Concerning the productivity, assessed as the maximum biomass yield at the end of the culture period, the first rank is occupied by Nephroselmis with ~3.0 g d.w./L, followed by Tetraselmis (2.0 g/L), Dunaliella (1.58 g/L), Amphidinium (1.19 g/L), and Asteromonas (0.7 g/L) with all values recorded at high light (8000 lux).